Andarilhos da esperança: estudo sobre a luta política impulsionada pela vida na rua e seus processos educativos sistematizada na experiência do Fórum da População de Rua de São Carlos/SP entre 2016 e 2017 - Almeida, Sara Ferreira de (2018)
The more than 100 thousand people living on the streets in Brazil, without fundamental rights access is the result of a life organization system whose primary elements are: profit and private property; individualism and social segregation. Reactions of the Homeless in face of this reality led to the institution of public policy focused on the group in 2009. Academic production, especially in the field of Education, did not focus on the conquest of these rights, trying to understand if the processes of organization of the group in the struggle their problem or in their maintenance. This study sought to address this gap by explore emerging educational processes in such practice. The methodological course was built in two moments. The first one followed the presuppositions of the Philosophy of Liberation of Enrique Dussel that contributed the narrative of three militants of the Forum of the Homeless and of the Homeless National Movement in Campinas. They shared their own experiences from childhood to adulthood and from that to political engagement, making it possible to understand that life on the street dehumanizes and creates the substratum to humanize, but does not necessarily achieve that purpose. The political struggle unfolds in the practical field in distinct ways classified as: political practice for, with and of the Homeless. Each of them forms their subjects and they can be representatives and supporters of the street. These categories are organized by the conception of politics and education of Enrique Dussel and Paulo Freire. Such authors argue that when the voice of victimized subjects is heard in the construction of political struggle, it becomes an instrument of destabilization of what is given. It was this premise that guided the second moment of the sustained methodological course on the Systematization of Experiences, a research procedure that seeks to overcome the totalization of hegemonic science that hides popular knowledge. Adopting this strategy and anchoring it in the thinking of Oscar Jara Holliday and Marco Raul Mejía allowed the analysis of the political action of the São Carlos Homeless Forum from february 2016 to january 2017. Field notes, personal memories, minutes of the monthly meetings, photographic images, interviews and talk wheels were sources of recording and data collection. The conclusion of the investigation provided the defense that in the practice of political struggle carried out by those who have a street trajectory and their supporters, a narrative and knowledge capable of forming a proper reference point of this experience, which is always diverse and collective, is produced. The identification of the processes of his institution allowed to point out contributions to the political-educational activities of this popular group, besides giving clues to the construction of a scientific praxis that comes from the domain of the totalization of academic knowledge about the popular.